Exhibit pays homage to local veterans Sherrie Holiman Grona - Grona, Sherri Holiman (Albuquerque, New Mexico Albuqueruqe Journal, 2007)
Newspaper article on Raton museum and the exhibits that will be showing to honor the people in Colfax County and Raton.
Master list item #: 143
File location is in the Raton file Cabinet
Keywords: McQueary, Kathy; Sanchez, Roger; Ghiglieri, Emilio; Mora, Frank; Mora, Rosie; Udall, Tom; Raton Museum; New Mexico Association of Museums; Air Force; Pacific Theater; Local History; Biography; Life and Customs; Pearl Harbor; Exhibit; Military memorabilia; World War I & II; Statue of Liberty; Old mining town; Raton, New Mexico; South Pacific; Brilliant, New Mexico; Colfax County